Growth and Short Term Egg Production of Two Exotic (Layer Type) and the Local Chickens Compared with Their F1 Inbred Progenies - Udeh , I.; Omeje, S.I. (International Journal of Poultry Science, 2011)
The objective of this study was to compare the growth and short term egg production of two exotic and the local chicken with those of their F1 inbred progenies in order to determine the effect of one generation of full sib mating on these traits. The two exotic chickens were H and N Brown Nick (strain 1) and Black Olympia (strain 2) while the local chicken was strain 3. The experimental birds were raised in deep litter pens from day old to 40 weeks of age. The coefficient of inbreeding of the three strains were as follows: strain 1 (10.80%), strain 2 (9.00%) and strain 3 (11.80%). Body weight, weight gain, age at first egg, age at peak egg production, egg weight, hen day rate and feed per dozen eggs were significantly (p<0.01) depressed in the two exotic (strains 1 and 2) but not in the local chicken except age at peak egg production. The parent consumed significantly (p<0.01) more feed to first egg compared with the inbred progeny of strain 1. The reverse was the case in strain 2. Total feed to first egg was similar in both generations of strain 3. The inbred progeny generation of the two exotic strains recorded more mortality compared with the parents. Both generations of strain 3 did not record any mortality during the laying period. It was concluded that generating replacement stock through inbreeding should be avoided in the exotic chicken but not in the local type.